Effect of Plyometric Training and Biological Maturation on Jump and Change of Direction Ability in Female Youth. Issue 10 (October 2021) - Davies, Michael J.; Drury, Benjamin; Ramirez-Campillo, Rodrigo; Chaabane, Helmi; Moran, Jason
Abstract : Abstract: Davies, MJ, Drury, B, Ramirez-Campillo, R, Chaabane, H, and Moran, J. Effect of plyometric training and biological maturation on jump and change of direction ability in female youth. J Strength Cond Res 35(10): 2690–2697, 2021—Biological maturation has been shown to affect male youths' responses to plyometric training (PT). However, to date, no researcher has examined the effect of maturation on the effects of PT in female youth. We undertook the first controlled intervention study to examine this, focusing on adaptive responses to countermovement jump (CMJ), reactive strength index (RSI), and change of direction (COD) performance in groups of female youth divided by maturation status (years from peak height velocity [PHV]). The training program lasted 7 weeks with subjects undertaking 2 sessions of PT per week. In the mid-PHV group, there was a small increase (effect size; 90% confidence interval = 0.40; −0.23 to 1.03) in CMJ performance. No changes were observed in the post-PHV group (0.02; −0.68 to 0.72). For RSI, there was a moderate increase in the mid-PHV group (0.94; 0.29–1.59) with only a trivial increase in the post-PHV group (0.06; −0.65 to 0.76). The intervention exerted no positive effect on COD performance in any group. Plyometric training seems to enhance CMJ and RSI in female youth, although the magnitude of adaptation could be affected by maturation status. A twice-per-week program of multidirectional jumping and hopping, with bilateral and unilateral components, can be used as a preparatory precursor to physical education classes or recreational sport.